2021
DOI: 10.9734/jpri/2021/v33i48a33242
|View full text |Cite
|
Sign up to set email alerts
|

Conservative Management of Cervical Rib- A Case Report

Abstract: Background: An additional rib that develops from the seventh cervical vertebra is known as a cervical rib, a congenital anomaly placed above the typical first rib, affecting 0.2- 0.5 percent of the total population. It may be seen on either the left or right sides. The majority of patients have little or no complaints and are identified by chance during an X-ray or CT scan. Due to the extreme compression on the arteries, veins and nerves caused by the position of the rib, which varies in shape and size, they m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Physical therapy has been shown to be effective in improving deltoid and bicep strength following C5 nerve root palsy and in managing mild lumbar PIVD conservatively. Kim SW et al's 2017 study reported on the successful conservative management of bilateral C5 nerve root palsy in a 58-year-old female patient [10].…”
Section: Discussionmentioning
confidence: 99%
“…Physical therapy has been shown to be effective in improving deltoid and bicep strength following C5 nerve root palsy and in managing mild lumbar PIVD conservatively. Kim SW et al's 2017 study reported on the successful conservative management of bilateral C5 nerve root palsy in a 58-year-old female patient [10].…”
Section: Discussionmentioning
confidence: 99%